Characterization of Rhizobia Isolated from Different Divergence Groups of Tropical Leguminosae by Comparative Polyacrylamide Gel Electrophoresis of their Total Proteins - Moreira, Fátima Maria de Souza; Gillis, Monique; Pot, Bruno; Kersters, Karel; Franco, Avílio Antônio (Systematic and Applied Microbiology, 1993)
In an attempt to determine the taxonomic position of and the relationships between some 800 strains of bradyrhizobia and rhizobia isolated from nodules of tropical leguminous plants in the Amazon region and Atlantic forests of Brazil, 171 strains (of which 120 were slow or very slow growers) were selected for study by sodium dodecyl sulphate polyacrylamide gel electrophoresis of proteins (SDS-PAGE). The strains were chosen to represent culturally different isolates from different divergence groups of Leguminosae. Appropriate type and reference strains and also seven tropical strains isolated from Phaseolus vulgaris were included for comparison. At a mean correlation coefficient (r) of 0.86, 23 protein electrophoretic clusters were obtained. The majority of the isolates grouped in a large cluster that contained the type strain of Bradyrhizobium japonicum. This cluster could be divided in 5 subclusters that correlated only to some degree with previously determined DNA homology groups. A few of the isolates could be equated with the species Rhizobium fredii (syn. Sinorhizobium fredii), R. galegae and R. loti but many could not be allocated to currently described taxa. No correlation was noted between clusters obtained and the divergence groups of Leguminosae from which the strains were isolated. © 1993, Gustav Fischer Verlag, Stuttgart · New York. All rights reserved.
Keywords: Bradyrhizobium; Nonhuman; Electrophoresis, Polyacrylamide Gel; Priority Journal; Rhizobium; Taxonomy; Bradyrhizobia; Bradyrhizobium; Bradyrhizobium Japonicum; Fabaceae; Phaseolus Vulgaris; Rhizobium; Rhizobium Galegae; Sinorhizobium Fredii